A method for surface strengthening of a cast steel special-shaped pipe fitting

CN119529638BActive Publication Date: 2026-09-04SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411794772.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2026-09-04
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

[0003]针对以上现有技术存在的问题,本发明的目的在于提供一种铸钢异形管件表面强化方法,该方法在铸钢异形管件基体表面制备耐高温、抗热震、结合力强的增强型功能涂膜,涂膜与基体结合强度高、隔热性能优异,且在高温震动工况下、不易发生开裂、变形、脱落等问题,隔热稳定性好

Benefits of technology

本发明通过涂膜对异形铸钢管件基体表面进行强化,涂膜功能层与基体之间结合力高、隔热性能好,能够有效贴附于异形铸钢管件的各个异形面、不会产生空气间隙,进而避免温度聚集点的形成,整个涂膜功能层的隔热性能优异;同时,本发明的涂膜与基体之间粘附性强、涂膜拉伸强度与抗断裂性能高,在高温-震动耦合的极端工况下,涂膜层不会出现裂纹、变形、脱落等问题,从而有效提升涂膜与基体的使用寿命及耐候性。此外,本申请涂膜施工工艺简单,能够在提高生产效率的同时、降低生产成本,从而扩大铸钢异形管件的适用场景、提高铸钢异形管件的应用率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529638B_ABST
    Figure CN119529638B_ABST
Patent Text Reader

Abstract

The application provides a cast steel special-shaped pipe surface strengthening method and relates to the cast steel surface strengthening field, and comprises the following steps: step one, surface pretreatment; step two, solution preparation: nano zirconium dioxide, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent and polyvinyl alcohol are sequentially added into deionized water and are stirred and mixed; step three, coating film preparation; and step four, solidification. The method is used for preparing the reinforced functional coating film with high-temperature resistance, thermal shock resistance and strong bonding force on the base surface of the cast steel special-shaped pipe, the coating film has high bonding strength with the base, excellent heat insulation performance, and is not prone to problems such as cracking, deformation and falling, has stable performance, long effect and can be used for the surface of the cast steel special-shaped pipe in various fields, and has wide application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface strengthening technology for cast steel, and in particular to a method for surface strengthening of cast steel irregular-shaped pipe fittings. Background Technology

[0002] Cast steel shaped pipe fittings are irregularly shaped or non-standard pipe fittings made of cast steel. They are characterized by their complex and diverse shapes, high strength and toughness, excellent machinability, good corrosion resistance, and strong structural integrity. Currently, some cast steel shaped pipe fittings mainly use multi-layered cladding materials for insulation. The cladding materials can effectively suppress radiative and convective heat transfer, thus significantly isolating heat transfer. However, because the surface of cast steel shaped pipe fittings is composed of many continuous irregular surfaces spliced ​​together, problems such as insufficient tightness of the cladding material and low bonding strength can easily occur, leading to air gaps. This not only reduces the insulation effect but also easily causes temperature accumulation within the gaps, resulting in safety hazards. In existing technologies, the solution is to use overlapping or staggered wrapping methods to cover different surfaces before applying an integrated outer layer. While this method can effectively avoid the formation of air gaps, increasing the thickness and amount of wrapping material not only increases the cost of the insulation material but also easily causes interference with adjacent components, greatly limiting the usable space. Meanwhile, existing technologies also use coatings to replace wrapping materials for heat insulation of cast steel shaped pipes. Although the coating can adhere tightly to the surface of the cast steel shaped pipe and avoid gaps between contact surfaces, under high-temperature and vibration conditions, the coating is prone to cracking and peeling. This results in the cast steel shaped pipe substrate losing protection, directly exposed to high temperatures, leading to aging, performance degradation, and even damage. In other words, existing coatings have poor heat insulation stability and poor resistance to complex environments (i.e., fatigue, high temperature, vibration, etc.). Summary of the Invention

[0003] To address the problems existing in the prior art, the present invention aims to provide a surface strengthening method for cast steel irregular pipe fittings. This method prepares a high-temperature resistant, thermal shock resistant, and strongly bonded reinforced functional coating on the surface of the cast steel irregular pipe fitting substrate. The coating has high bonding strength with the substrate, excellent thermal insulation performance, and is not prone to cracking, deformation, or peeling under high-temperature vibration conditions, exhibiting good thermal insulation stability.

[0004] The objective of this invention is achieved through the following technical solution: A method for surface strengthening of cast steel irregular-shaped pipe fittings includes: Step 1: Surface pretreatment: Sandblasting is performed on the outer wall of the cast steel irregular pipe fitting; Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide (MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water and mixed evenly using a mechanical stirrer. Step 3, Coating preparation: Use a spray gun to spray the uniformly mixed solution from Step 2 onto the surface of the pretreated cast steel shaped pipe fitting from Step 1, let it stand until the solution no longer flows, then spray again, repeating the spraying process 5 to 15 times. Step 4, Curing: Place the cast steel shaped pipe fittings that have been sprayed in Step 3 into an oven for curing treatment, and then take them out to obtain pipe fittings with a reinforced coating on the surface.

[0005] Based on further optimization of the above scheme, the pressure of sandblasting in step one is 1 to 4 MPa.

[0006] Based on further optimization of the above scheme, the weight percentages of the nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol are: 15%–25%, 8%–15%, 3%–6%, 2%–4%, 15%–25%, 2%–3%, 2%–3%, 1%–2%, with the remainder being deionized water.

[0007] By compounding nano-zirconia, aluminosilicate fibers, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol, nano-zirconia particles can be uniformly dispersed on the surface of aluminosilicate fibers. Aluminosilicate fibers themselves have the characteristics of low thermal conductivity, high strength, and high toughness. During the coating preparation process, using a specific ratio, the nano-zirconia particles are adsorbed onto the surface of the aluminosilicate fibers and exhibit a clustered distribution, thereby effectively hindering heat transfer in the coating and improving thermal insulation performance. At the same time, the uniformly distributed clustered structure can also improve the density of the coating, thereby deflecting and bridging the crack propagation when cracks occur under high-temperature vibration conditions, further improving the toughness of the coating and the interfacial bonding strength between the coating and the substrate grains, and avoiding problems such as cracking and peeling of the coating under high-temperature vibration conditions.

[0008] Based on further optimization of the above scheme, the modified epoxy resin includes polyurethane, polysulfone, graphene oxide, E20 bisphenol A type epoxy resin and deionized water; wherein, the weight percentages of polyurethane, polysulfone, graphene oxide and E20 bisphenol A type epoxy resin are 10%–20%, 5%–15%, 0.5%–1%, and 20%–30%, respectively, and the remainder is deionized water.

[0009] By blending polyurethane, polysulfone, graphene oxide, and E20 bisphenol A epoxy resin, the interfacial bonding and interphase adhesion are enhanced through the interaction between the polar groups such as urethane groups of polyurethane and the polar groups such as sulfone groups and ether bonds of polysulfone and E20 bisphenol A epoxy resin. This effectively improves the overall tensile strength and fracture resistance of the modified epoxy resin. Furthermore, polysulfone and graphene oxide effectively improve the dispersibility of polyurethane in E20 bisphenol A epoxy resin, preventing problems caused by excessive crosslinking density or excessive aggregation and entanglement of polyurethane and E20 bisphenol A epoxy resin. Problems such as excessive brittleness and excessive viscosity (excessive brittleness or viscosity of epoxy resin not only makes subsequent spraying difficult, but also easily leads to cracking and peeling of the coating under high temperature and vibration conditions) are eliminated. This method facilitates subsequent spraying and further enhances the stability of the coating under high temperature and vibration conditions. At the same time, the modified epoxy resin formed by blending specific formulations can effectively form a uniform three-dimensional network structure, promote the formation of nano-zirconia and aluminum silicate fiber clusters, thereby improving the toughness of the final coating and the strong adhesion between the coating and the substrate, further avoiding problems such as cracking and peeling of the coating.

[0010] Based on further optimization of the above scheme, the mixing speed of the mechanical stirrer in step two is 500-1200 r / min, and the mixing time is 20-30 min.

[0011] Based on further optimization of the above scheme, the environment for coating preparation in step three is: temperature not less than 20℃ and humidity not greater than 60%.

[0012] Based on further optimization of the above scheme, in step three, the central axis of the spray gun is perpendicular to the surface to be sprayed, the distance between the spray gun and the surface to be sprayed is 15-25cm, and the settling time after spraying is 1-2h.

[0013] Based on further optimization of the above scheme, the curing treatment in step four adopts a staged heating process, that is, after closing the furnace door, first heat up to 75-85℃ and hold for 0.8-1.2h, then heat up to 95-105℃ and hold for 0.8-1.2h, then heat up to 140-160℃ and hold for 1-1.4h, and finally heat up to 170-190℃ and hold for 2.8-3.2h.

[0014] By controlling the temperature gradient through staged heating, problems such as violent intermolecular reactions and uneven curing caused by excessive temperature differences or instantaneous high temperatures can be avoided. It also effectively prevents the generation of instantaneous thermal stress between molecules, which can lead to coating cracks and surface wrinkles. Furthermore, the staged heating effectively activates the functional groups in nano-zirconia, aluminum silicate fiber, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol, increasing the tightness of intermolecular linkages and promoting full reaction between functional groups. This enhances the integrity of the entire cross-linked network, forming a complete and effective three-dimensional network structure. This improves the overall thermal insulation performance and toughness of the coating while ensuring tight bonding between coating layers, effectively preventing delamination, wrinkles, deformation, and peeling during coating preparation.

[0015] Based on further optimization of the above scheme, when taking out the pipe with the surface coated with the reinforced coating in step four, turn off the heating power of the oven and wait for the oven temperature to drop below 60°C.

[0016] The following are the technical effects of the present invention: This invention strengthens the surface of irregularly shaped cast steel pipe fittings through a coating. The coating layer exhibits high adhesion to the substrate and excellent thermal insulation performance, effectively adhering to all irregular surfaces of the pipe fittings without creating air gaps, thus preventing the formation of temperature accumulation points. The entire coating layer demonstrates superior thermal insulation performance. Simultaneously, the coating exhibits strong adhesion to the substrate, high tensile strength, and high fracture resistance. Under extreme conditions of high temperature and vibration coupling, the coating layer does not crack, deform, or peel off, effectively improving the service life and weather resistance of both the coating and the substrate. Furthermore, the coating application process is simple, improving production efficiency while reducing production costs, thereby expanding the application scenarios and increasing the utilization rate of irregularly shaped cast steel pipe fittings. Attached Figure Description

[0017] Figure 1 This is a flowchart of the surface strengthening method for cast steel irregular pipe fittings in an embodiment of the present invention. Detailed Implementation

[0018] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0019] Example 1: A method for surface strengthening of cast steel irregular-shaped pipe fittings includes: Step 1: Surface pretreatment: Sandblast the outer wall of the cast steel irregular pipe fitting at a pressure of 1 MPa; visually inspect the surface after sandblasting to ensure that the color is uniform and there are no areas with metallic luster. Then blow away the sand and dust.

[0020] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 15%, 8%, 3%, 2%, 15%, 2%, 2%, and 1%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 500 rpm for 30 minutes. The modified epoxy resin includes polyurethane, polysulfone, graphene oxide, E20 bisphenol A type epoxy resin and deionized water; the weight percentages of polyurethane, polysulfone, graphene oxide and E20 bisphenol A type epoxy resin are 10%, 5%, 0.5% and 20% respectively, and the remainder is deionized water.

[0021] Step 3, Coating Preparation: In an environment with a temperature not less than 20℃ (e.g., temperature of 20℃) and humidity not greater than 60% (e.g., humidity of 60%), use a spray gun to spray the uniformly mixed solution from Step 2 onto the surface of the pretreated cast steel shaped pipe fitting from Step 1. During spraying, the central axis of the spray gun is perpendicular to the surface to be sprayed, and the distance between the spray gun and the surface to be sprayed is 15cm. Let it stand for 1 hour until the solution no longer flows, then spray again. Repeat the spraying process 5 times. During the spraying process, a non-uniformity of ±30μm is allowed, and areas with uneven spraying can be touched up with a scraper.

[0022] Step 4: Curing: Place the cast steel shaped pipe fittings coated in Step 3 into an oven for curing. The curing process uses a staged heating method: after closing the oven door, first raise the temperature to 75℃ and hold for 0.8 hours, then raise it to 95℃ and hold for 0.8 hours, then raise it to 140℃ and hold for 1 hour, and finally raise it to 170℃ and hold for 2.8 hours. Afterward, turn off the oven's heating power and wait for the oven temperature to drop below 60℃ before removing the pipe fittings with the reinforced coating. The total coating thickness, measured using measuring tools, is 0.8 mm.

[0023] Example 2: A method for surface strengthening of cast steel irregular-shaped pipe fittings includes: Step 1: Surface pretreatment: Sandblast the outer wall of the cast steel irregular pipe fitting at a pressure of 2.5 MPa; visually inspect the surface after sandblasting to ensure that the color is uniform and there are no areas with metallic luster. Then blow away the sand and dust.

[0024] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 10%, 11.5%, 4.5%, 3%, 10%, 2.5%, 2.5%, and 1.5%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 850 r / min for 25 min. The modified epoxy resin includes polyurethane, polysulfone, graphene oxide, E20 bisphenol A type epoxy resin and deionized water; the weight percentages of polyurethane, polysulfone, graphene oxide and E20 bisphenol A type epoxy resin are 15%, 10%, 0.7% and 25% respectively, and the remainder is deionized water.

[0025] Step 3, Coating Preparation: In an environment with a temperature not less than 20℃ (e.g., 25℃) and humidity not greater than 60% (e.g., 55%), use a spray gun to spray the uniformly mixed solution from Step 2 onto the surface of the pretreated cast steel shaped pipe fitting from Step 1. During spraying, the central axis of the spray gun is perpendicular to the surface to be sprayed, and the distance between the spray gun and the surface to be sprayed is 20cm. Let it stand for 1.5 hours until the solution no longer flows, then spray again. Repeat the spraying process 10 times. During the spraying process, a non-uniformity of ±30μm is allowed, and areas with uneven spraying can be touched up with a scraper.

[0026] Step 4: Curing: Place the cast steel shaped pipe fittings coated in Step 3 into an oven for curing. The curing process uses a staged heating process: after closing the oven door, first raise the temperature to 80℃ and hold for 1 hour, then raise it to 100℃ and hold for 1 hour, then raise it to 150℃ and hold for 1.2 hours, and finally raise it to 180℃ and hold for 3 hours. Afterward, turn off the oven's heating power and wait for the oven temperature to drop below 60℃ before removing the pipe fittings with the reinforced coating. The total coating thickness, measured using measuring tools, is 1.5 mm.

[0027] Example 3: A method for surface strengthening of cast steel irregular-shaped pipe fittings includes: Step 1: Surface pretreatment: Sandblast the outer wall of the cast steel shaped pipe fitting with a sandblasting pressure of 1-4 MPa; visually inspect the surface after sandblasting to ensure that the color is uniform and there are no areas with metallic luster, and then blow away the sand and dust.

[0028] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconium dioxide, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 25%, 15%, 6%, 4%, 25%, 3%, 3%, and 2%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 1200 r / min for 20 min. The modified epoxy resin includes polyurethane, polysulfone, graphene oxide, E20 bisphenol A type epoxy resin and deionized water; the weight percentages of polyurethane, polysulfone, graphene oxide and E20 bisphenol A type epoxy resin are 20%, 15%, 1% and 30% respectively, and the remainder is deionized water.

[0029] Step 3, Coating Preparation: In an environment with a temperature not less than 20℃ (e.g., temperature of 30℃) and humidity not greater than 60% (e.g., humidity of 50%), use a spray gun to spray the uniformly mixed solution from Step 2 onto the surface of the pretreated cast steel shaped pipe fitting from Step 1. During spraying, the central axis of the spray gun is perpendicular to the surface to be sprayed, and the distance between the spray gun and the surface to be sprayed is 25cm. Let it stand for 2 hours until the solution no longer flows, then spray again. Repeat the spraying process 15 times. During the spraying process, a non-uniformity of ±30μm is allowed, and areas with uneven spraying can be touched up with a scraper.

[0030] Step 4: Curing: Place the cast steel shaped pipe fittings coated in Step 3 into an oven for curing. The curing process uses a staged heating method: after closing the oven door, first raise the temperature to 85℃ and hold for 1.2 hours, then raise it to 105℃ and hold for 1.2 hours, then raise it to 160℃ and hold for 1.4 hours, and finally raise it to 190℃ and hold for 3.2 hours. Afterward, turn off the oven's heating power and wait for the oven temperature to drop below 60℃ before removing the pipe fittings with the reinforced coating. The total coating thickness, measured using measuring tools, is 2.2 mm.

[0031] Comparative Example 1: A method for surface strengthening of pipe fittings, comprising: Step 1, Surface Pretreatment: This step is consistent with Step 1 in Example 2.

[0032] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, E20 bisphenol A epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconium dioxide, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, E20 bisphenol A epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 10%, 11.5%, 4.5%, 3%, 10%, 2.5%, 2.5%, and 1.5%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 850 r / min for 25 min.

[0033] Step 3, Coating Preparation: This step is consistent with Step 3 in Example 2.

[0034] Step 4, Curing: This step is consistent with Step 4 in Example 2.

[0035] The total thickness of the coating, as measured by the measuring tool, is 1.5 mm.

[0036] Comparative Example 2: A method for surface strengthening of pipe fittings, comprising: Step 1, Surface Pretreatment: This step is consistent with Step 1 in Example 2.

[0037] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 10%, 11.5%, 4.5%, 3%, 10%, 2.5%, 2.5%, and 1.5%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 850 r / min for 25 min. The modified epoxy resin includes polyurethane, graphene oxide, E20 bisphenol A type epoxy resin and deionized water; the weight percentages of polyurethane, graphene oxide and E20 bisphenol A type epoxy resin are 15%, 0.7% and 25% respectively, and the remainder is deionized water.

[0038] Step 3, Coating Preparation: This step is consistent with Step 3 in Example 2.

[0039] Step 4, Curing: This step is consistent with Step 4 in Example 2.

[0040] The total thickness of the coating, as measured by the measuring tool, is 1.5 mm.

[0041] Comparative Example 3: A method for surface strengthening of pipe fittings, comprising: Step 1, Surface Pretreatment: This step is consistent with Step 1 in Example 2.

[0042] Step 2, Solution Preparation: Nano-zirconia, aluminum silicate fiber, and iron oxide are sequentially added... Fe 2 O 3) Filler, magnesium oxide ( MgO The filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were added to deionized water. The weight percentages of nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol were 10%, 11.5%, 4.5%, 3%, 10%, 2.5%, 2.5%, and 1.5%, respectively, with the remainder being deionized water. The mixture was stirred evenly using a mechanical stirrer (any conventional mechanical stirrer in this field is acceptable) at a speed of 850 r / min for 25 min. The modified epoxy resin includes polyurethane, polysulfone, E20 bisphenol A type epoxy resin and deionized water; the weight percentages of polyurethane, polysulfone, and E20 bisphenol A type epoxy resin are 15%, 10%, and 25%, respectively, with the remainder being deionized water.

[0043] Step 3, Coating Preparation: This step is consistent with Step 3 in Example 2.

[0044] Step 4, Curing: This step is consistent with Step 4 in Example 2.

[0045] The total thickness of the coating, as measured by the measuring tool, is 1.5 mm.

[0046] Comparative Example 4: A method for surface strengthening of pipe fittings, comprising: Step 1, Surface Pretreatment: This step is consistent with Step 1 in Example 2.

[0047] Step 2, Solution Preparation: This step is consistent with Step 2 in Example 2.

[0048] Step 3, Coating Preparation: This step is consistent with Step 3 in Example 2.

[0049] Step 4: Curing: Place the cast steel shaped pipe fittings, which have been sprayed in Step 3, into an oven for curing. The curing process uses a staged heating process: after closing the oven door, first raise the temperature to 100℃ and hold for 2 hours, then raise the temperature to 180℃ and hold for 4.2 hours. Subsequently, turn off the heating power of the oven and wait for the oven temperature to drop below 60℃ before removing the pipe fittings with the reinforced coating.

[0050] The total thickness of the coating, as measured by the measuring tool, is 1.6 mm.

[0051] The adhesion strength of the coatings in Examples 1-3 and Comparative Examples 1-4 was tested using the pull-out method. First, the pipes coated with the reinforcing coating in Examples 1-3 and Comparative Examples 1-4 were fixed onto the bonding fixture of a tensile testing machine (ensuring a secure installation and uniform application of tensile force to the bonding interface). Then, a tensile force was applied at a certain speed, typically between 0.1 and 10 mm / min. The tensile force and displacement values ​​were recorded in real time during the tensile process. The maximum tensile force at the point of bonding interface failure was recorded, and the corresponding adhesion strength of the coating was obtained. Z (Unit: MPa ): ; In the formula: F max This indicates the maximum tensile force value recorded at the point of bond failure (unit: ...). N ); S Indicates the bonding area (unit: m²) 2 ); Furthermore, the thermal insulation performance of the pipe fittings coated with the reinforced coating obtained in Examples 1-3 and Comparative Examples 1-4 was tested. Thermocouples were uniformly arranged on the outer wall of the pipe fittings coated with the reinforced coating, and the inner cavity of the pipe fittings was heated. The final test results are shown in Table 1 below: Table 1:

[0052] As shown in the table above, the adhesion and heat insulation performance of the coating can be effectively improved by using the coating film with the specific formula of this invention and the specific staged heating and curing process.

[0053] For further thermal insulation performance testing, a covering layer with a thickness of 2-10 cm (3 cm in this embodiment) was used to cover the outer wall of the pipe fitting coated with the reinforced coating to obtain a thermally insulated irregular pipe fitting. The covering layer can be any one of rock wool, ceramic glass wool, polystyrene foam, or polyurethane foam (ceramic glass wool was used in this embodiment). The outer walls of the pipe fittings coated with the reinforced coating in Examples 1-3 and Comparative Examples 1-4 were covered respectively, and the thermal insulation performance of the covering was tested. The test results are shown in Table 2 below: Table 2

[0054] As shown in the table above, the coating film with the specific formula of this invention and the specific staged heating and curing process, when combined with the coating layer, can effectively improve the overall thermal insulation performance of the pipe fitting.

Claims

1. A method for surface strengthening of cast steel irregular-shaped pipe fittings, characterized in that: include: Step 1: Surface pretreatment: Sandblasting is performed on the outer wall of the cast steel irregular pipe fitting; Step 2, Solution preparation: Nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol are added to deionized water in sequence and mixed evenly using a mechanical stirrer. In the solution, the weight percentages of nano-zirconia, aluminum silicate fiber, iron oxide filler, magnesium oxide filler, modified epoxy resin, sodium hexametaphosphate, siloxane coupling agent, and polyvinyl alcohol are: 15%–25%, 8%–15%, 3%–6%, 2%–4%, 15%–25%, 2%–3%, 2%–3%, and 1%–2%, with the remainder being deionized water; the modified epoxy resin includes polyurethane, polysulfone, graphene oxide, E20 bisphenol A type epoxy resin, and deionized water; in the modified epoxy resin, the weight percentages of polyurethane, polysulfone, graphene oxide, and E20 bisphenol A type epoxy resin are 10%–20%, 5%–15%, 0.5%–1%, and 20%–30%, with the remainder being deionized water; Step 3, Coating preparation: Use a spray gun to spray the uniformly mixed solution from Step 2 onto the surface of the pretreated cast steel shaped pipe fitting from Step 1, let it stand until the solution no longer flows, then spray again, repeating the spraying process 5 to 15 times. Step 4, Curing: Place the cast steel shaped pipe fittings that have been sprayed in Step 3 into an oven for curing. The curing process adopts a staged heating process, that is, after closing the oven door, first raise the temperature to 75-85℃ and hold for 0.8-1.2h, then raise the temperature to 95-105℃ and hold for 0.8-1.2h, then raise the temperature to 140-160℃ and hold for 1-1.4h, and finally raise the temperature to 170-190℃ and hold for 2.8-3.2h. Then take them out and obtain the pipe fittings with a reinforced coating on the surface.

2. The surface strengthening method for cast steel irregular-shaped pipe fittings according to claim 1, characterized in that: The pressure for sandblasting in step one is 1-4 MPa.

3. The surface strengthening method for cast steel irregular-shaped pipe fittings according to claim 2, characterized in that: In step two, the mechanical stirrer operates at a speed of 500–1200 r / min and a stirring time of 20–30 min.

4. The surface strengthening method for cast steel irregular-shaped pipe fittings according to claim 1, characterized in that: The environment for coating preparation in step three is: temperature not less than 20℃ and humidity not greater than 60%.

5. The surface strengthening method for cast steel irregular-shaped pipe fittings according to claim 4, characterized in that: In step three, during spraying, the central axis of the spray gun is perpendicular to the surface to be sprayed, the distance between the spray gun and the surface to be sprayed is 15-25cm, and the settling time after spraying is 1-2h.

Citation Information

Patent Citations

  • Anticorrosive production process of oil pipe

    CN102327859A

  • Nano anti-corrosion thermal insulation coating and preparation method thereof

    CN109233555A